Ajustes motivacionales que han realizado en sus proyectos de vida cuatro jóvenes que lograron ser futbolistas profesionales (2012)
The present investigation establishes the meaning at motivational level and life project of 4 people who trained soccer in different sports schools, and did not reach their goal of being professional soccer players in Colombia. The methodology used is qualitative and descriptive design. The participants were four (4) young people, where (1) from Chocó, (1) from Cali and (2) Bogotá, Colombia; who did not have the possibility of becoming professional soccer players, even though it was part of their life project. The technique chosen to collect the information was the open interview and inductive categorization was used for its analysis. The results allowed us to explore the experiences and expectations that they had in this period, as well as the motivational adjustments to reorient their life project.